KORUPSI DAN PENANAMAN MODAL ASING: PERBAIKAN KELEMBAGAAN - Ratna Christianingrum (Pusat Kajian Anggaran, 2023)
Scholars have studied the impact of corruption on foreign direct investment (FDI). Some studies provide evidence of a negative link between corruption and FDI, while others fail to find any significant relationship. This study examines the impact of corruption on FDI in Indonesia. The data used for this study is the corruption perception index from Transparency International and the FDI for Indonesia from CEIC. The data will be analyzed using the regression method to estimate the impact of corruption on FDI. This study shows that the corruption perception index (CPI) significantly and negatively affects FDI in Indonesia. A low level of CPI implies a high level of corruption. The findings of this study support the “grease the wheels” hypothesis. Corruption can be a ‘grease of the wheels’ for accelerating economic expansion in Indonesia. This condition is not a good thing. So, institutional improvement is needed to reduce corrupt practices. It includes reducing licensing procedures and improving the supervision system. Budget support is needed.